Lefkoşa Bölgesinde Bulunan İlkokul 4. ve 5. Sınıfta Öğrenim Gören Öğrencilerin Süt ve Süt Ürünlerinin Tüketimi, Antropometrik Ölçümlerinin ve Beslenme Durumlarının Saptanması - Sözcü, Eda (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
In this research was carried out during the 2014-2015 academic year in May at seventeen government primary schools located in the Nicosia area. 1390 students aged 9-13 were included. The students that took place in the research consisted of 731 male and 659 female. The calculations of the research show students overall use of nutrition, the habit of using milk and dairy products, the anthropometric measurements of milk and dairy products were questioned but especially daily use of milk, energy, carbohydrate, protein, fat and calcium. A questionnaire form was applied to determine dietary food intakes for three days. The result of the BMI percentage is <15 which shows 3.4% were male and 5.6% were female students. The normal weight (>15-<85) of male and female students show the ratio of 59.4% and 70.6%. The ratio of light overweight male students were 20.0% and 13.4% were female students. Male students habit of using milk was 91.9% whereas only 90.3% of female students used milk every day. The use of yoghurt by male students was 79.8% and female students was 78.6%. 78% of male and 79.8% of female students used cheese daily but preferably halloumi (80.9%). The statistics showed that 58.7% of male students and 56.4% of female students buy milk and dairy products from school canteens. The study shows students’ daily energy intake, protein, carbohydrate, fat from milk and dairy products in (%) accordance with milk consumption of the students. It also shows the daily amount of energy, CHO, protein, fat and calcium needed. Nutrition education should be given to change children’s eating habits. Keywords: Used milk and dairy products habits, Intake of energy.

ÖZ: Bu araştırma, Mayıs 2014-2015 tarihleri arasında Lefkoşa bölgesinde bulunan 17 devlet ilkokulunda öğrenim gören 9-13 yaş grubu erkek (n:731) ve kız (n:659) toplam 1390 öğrenci üzerinde yapılmıştır. Araştırmada öğrencilerin genel beslenme durumları, süt ve süt ürünlerinin tüketim alışkanlıkları, antropometrik ölçümleri sorgulanmış olup süt ve süt ürünlerinin ve özellikle süt tüketiminin günlük enerji, CHO, protein, yağ ve kalsiyum miktarlarının ne kadarını karşıladığı hesaplanmıştır. Anket formu ile üç günlük besin tüketimleri incelenmiştir. Erkek öğrencilerin %3.4’ünün, kızların ise %5.6’sının BKI (kg/m2) persentil değeri <15’dır. Normal ağırlıkta (>15-<85) olan erkek ve kızların oranı sırasıyla %59.4 ve %70.6’dır. Hafif şişman erkeklerin oranı %20.0 ve hafif şişman kızların oranı ise %13.4’tür. Erkek öğrencilerin her gün süt tüketim alışkanlığı %91.9 iken kızların %90.3’dür. Erkek öğrencilerin yoğurt tüketme alışkanlığı %79.8 ve kızların %78.6’dır. Erkeklerin %78.0’i, kızların %79.8’i peynir tüketmekte olup en fazla hellim tercih edilmektedir (%80.9). Okul kantinlerinde süt ve süt ürünleri satın alan erkek öğrencilerin oranı %58.7 iken %56.4’ü kız çocuklarıdır. Çocukların beslenme alışkanlıklarını değiştirmelerine yönelik olarak beslenme eğitimleri verilmeli. Anahtar Kelimeler: Süt ve süt ürünleri tüketim alışkanlığı, Enerji alımı.
Beslenme ve Diyetetik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Beslenme ve Diyetetik Bölümü, 2017. Tez Danışmanı: Prof. Dr. Perihan Arslan.
Keywords: Beslenme ve Diyetetik; Beslenme-Süt ve Süt Ürünleri; Süt ve süt ürünleri tüketim alışkanlığı; Enerji alımı